Response adaptive mechanisms of three mangrove (Avicennia marina, Aegiceras corniculatum, and Bruguiera gymnorrhiza) plants to waterlogging stress revealed by transcriptome analysis - Su, Bo-Yu; Wang, You-Shao; Sun, Cui-Ci (Frontiers in Marine Science, 2022)
Distributed in different elevations of the intertidal zone, mangrove plants suffer different periods of flooding, and with varied adaptability to waterlogging from the physiological structure to the metabolic mechanism. Associated with species distribution, transcriptome sequencing was performed to explore the interspecific differences of molecular response mechanisms among Avicennia marina, Aegiceras corniculatum, and Bruguiera gymnorrhiza under waterlogging stress. Results showed that the counts of differentially expressed genes (DEGs) in A. Marina were the highest after stress, followed by Ae. corniculatum and B. gymnorrhiza. It was found that the functions of genes with high differential expression folds (more than eight folds) in the three plants could be classified into four categories: structural regulation, transport, biosynthesis, and protection. It was also found that A. Marina has strong regulation ability in the metabolic process, which can guarantee energy supply and maintain active biosynthesis under waterlogging conditions. In addition, A. Marina was activated in the ethylene synthesis pathway to promote aerenchyma formation and to avoid root tissue hypoxia. Being different from A. Marina and B. gymnorrhiza, Ae. corniculatum down-regulated the XET, SAMS, and ACCO genes, which were involved in the cell wall regulation or ethylene formation that might indicate a different adaptive mechanism. Alcohol dehydrogenase (ADH) and lactate dehydrogenase (LDH) were cloned from A. Marina, Ae. corniculatum, and B. gymnorrhiza. The cloned genes were named as AmADH, AmLDH, AcADH, AcLDH, BgADH, and BgLDH, respectively. qRT-PCR detection verified that LDHs and ADHs were involved in the response of mangrove plants to waterlogging stress, and interspecific difference was observed. The expressions of AcADH and AcLDH were the most prominent. Combined with transcriptome, it was considered that Ae. corniculatum was more dependent on the expression of AcADH and AcLDH that might compensate the weakness of cell wall regulation, whereas A. Marina was more dependent on the regulation of cell structure reversely.